Projektiranje sklopa za generiranje referentnog napona i struje u 180 nm CMOS tehnologiji : završni rad - Osmanović, David (D. Osmanović, 2019)
Sažetak na hrvatskom: Microelectronics and integrated circuits represent the backbone of modern civilization. Reference voltage and current generators and reference resistors are basic building blocks of integrated circuits. The topic of this thesis is the design of a reference voltage and current generator in 180-nm CMOS technology. This circuit generates two referent voltages, one proportional to absolute temperature (PTAT) and the other one constant with temperature (CWT). The nominal value of the PTAT voltage is 0.35 V, while the CWT voltage is 0.6 V. The circuit also generates two 50 nA PTAT currents. The nominal supply voltage is 1.2 V and the nominal current consumption is 250 nA. The goal is to ensure a successful startup of the circuit when the supply voltage transitions from 0 to 1.2 V for the rise time between 1 us and 1 ms. Also, it is necessary to perform a temperature analysis in the range of -40 degrees C to 125 degrees C and corner analysis. It needs to be ensured that the circuit can start when the enable signal EN is high, and powers off when the enable goes low. Finally, all circuit characteristics have to be represented in graphical and tabular form.